Imaging: Guiding the Clinical Translation of Cardiac Stem Cell Therapy - Nguyen, Patricia K. (2011)
Stem cells have been touted as the holy grail of medical therapy with promises to regenerate cardiac tissue, but it appears the jury is still out on this novel therapy. Using advanced imaging technology, scientists have discovered that these cells do not survive nor engraft long-term. In addition, only marginal benefit has been observed in large animal studies and human trials. However, all is not lost. Further application of advanced imaging technology will help scientists unravel the mysteries of stem cell therapy and address the clinical hurdles facing its routine implementation. In this review, we will discuss how advanced imaging technology will help investigators better define the optimal delivery method, improve survival and engraftment, and evaluate efficacy and safety. Insights gained from this review may direct the development of future preclinical investigations and clinical trials.